Resisting the Heat: Bacterial Disaggregases Rescue Cells From Devastating Protein Aggregation - Katikaridis, Panagiotis; Bohl, Valentin; Mogk, Axel (Frontiers in Molecular Biosciences, 2021)
Bacteria as unicellular organisms are most directly exposed to changes in environmental growth conditions like temperature increase. Severe heat stress causes massive protein misfolding and aggregation resulting in loss of essential proteins. To ensure survival and rapid growth resume during recovery periods bacteria are equipped with cellular disaggregases, which solubilize and reactivate aggregated proteins. These disaggregases are members of the Hsp100/AAA+ protein family, utilizing the energy derived from ATP hydrolysis to extract misfolded proteins from aggregates via a threading activity. Here, we describe the two best characterized bacterial Hsp100/AAA+ disaggregases, ClpB and ClpG, and compare their mechanisms and regulatory modes. The widespread ClpB disaggregase requires cooperation with an Hsp70 partner chaperone, which targets ClpB to protein aggregates. Furthermore, Hsp70 activates ClpB by shifting positions of regulatory ClpB M-domains from a repressed to a derepressed state. ClpB activity remains tightly controlled during the disaggregation process and high ClpB activity states are likely restricted to initial substrate engagement. The recently identified ClpG (ClpK) disaggregase functions autonomously and its activity is primarily controlled by substrate interaction. ClpG provides enhanced heat resistance to selected bacteria including pathogens by acting as a more powerful disaggregase. This disaggregase expansion reflects an adaption of bacteria to extreme temperatures experienced during thermal based sterilization procedures applied in food industry and medicine. Genes encoding for ClpG are transmissible by horizontal transfer, allowing for rapid spreading of extreme bacterial heat resistance and posing a threat to modern food production.